DIMENSIONS OF FILOSOFIS IN THE MANAGEMENT OF ISLAM: CHALLENGES AND OPPORTUNITIES - Faizah, Nur; Zainuddin , Zainuddin; Mutmainnah, Mutmainnah (Antis-Publisher, 2024)
This study aims to explore the opportunities and challenges in integrating philosophical values ​​such as justice, honesty, responsibility, and spirituality in Islamic educational management. Using a qualitative approach and case study design, data were collected through in-depth interviews, participant observation, and document analysis from several Islamic educational institutions. The results of the study indicate that resistance to change, limited resources, lack of understanding, and minimal community support are the main challenges faced in implementing philosophical values. However, there is a great opportunity to develop more inclusive and ethical educational management through increasing awareness and education about philosophical values, developing a value-based curriculum, and strengthening the commitment of educational leaders and community participation. The implications of this study indicate that with the right strategies, Islamic educational institutions can overcome these obstacles and improve the quality of their educational management. This study makes a significant contribution to the literature on Islamic educational management and offers practical guidance for educational institutions in integrating philosophical values ​​into their daily management policies and practices.